Expression of ACE2, Soluble ACE2, Angiotensin I, Angiotensin II and Angiotensin-(1-7) Is Modulated in COVID-19 Patients - Osman, Ikram Omar; Melenotte, Cléa; Brouqui, Philippe; Million, Matthieu; Lagier, Jean-Christophe; Parola, Philippe; Stein, Andréas; La Scola, Bernard; Meddeb, Line; Mege, Jean-Louis; Raoult, Didier; Devaux, Christian A. (Frontiers in Immunology, 2021)
Although SARS-CoV-2 is primarily a pulmonary-tropic virus, it is nonetheless responsible for multi-organ failure in patients with severe forms of COVID-19, particularly those with hypertension or cardiovascular disease. Infection requires virus binding to the angiotensin I converting enzyme 2 (ACE2) monocarboxypeptidase, a regulator of blood pressure homeostasis through its ability to catalyze the proteolysis of Angiotensin II (AngII) into Ang(1-7). Although assumed, it had not been proven so far whether the SARS-CoV-2 replication in COVID-19 patients could modulate the expression of the ACE2 receptor and/or the AngII plasma levels. We demonstrate here, that in COVID-19 patients the ACE2 mRNA expression is markedly reduced in circulating blood cells. This ACE2 gene dysregulation mainly affects the monocytes which also show a lower expression of membrane ACE2 protein. Moreover, a significant decrease in soluble ACE2 plasma levels is observed in COVID-19 patients, whereas the concentration of sACE2 returns to normal levels in patients recovered from COVID-19. In the plasma of COVID-19 patients, we also found an increase in AngI and AngII. On the other hand, the plasma levels of Ang(1-7) remains almost stable in COVID-19 patients. Despite the Ang(1-7) presence in the plasma of COVID-19 patients it seems insufficient to prevent the effects of massive AngII accumulation. These are the first direct evidence that the SARS-CoV-2 may affect the expression of blood pressure regulators with possible harmful consequences on COVID-19 outcome.